Iowa RBA, July 22, 1996 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for July 22, 1996. Highlights of the update include the continued presence of a Black-headed Gull and a sighting of a Red-necked Grebe. Also of note was the observation of a Black Swan in the Carroll area, the release of two immature Trumpeter Swans at Black Hawk Lake, and the good shore birding at Island View Park near Rathbun Lake. Also included are handwritten notes for the next week's update with sightings of Red Crossbills, a Ruddy Shelduck, and a Pine Siskin. Epson - sheet feed/flatbed